BIOTEKNOLOGI : PERKEMBANGAN YANG TERTINGGAL DI DUNIA ISLAM - Hudha, Atok miftachul (Jurnal Bestari, 2001)
Althought, the holy book has some suggestions to enhance the science, in fact, the intellectual moslem has not indicate their write to develop science and technology yet. Primarily in the biotechnological researches. There are several factors cause their obstacles of developing the